2022
DOI: 10.1016/j.smrv.2021.101582
|View full text |Cite
|
Sign up to set email alerts
|

School start times and academic achievement - A systematic review on grades and test scores

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 87 publications
0
8
0
2
Order By: Relevance
“…For example, prior research in the United States has found that earlier course timing decreases grades among college students (Carrell et al, 2011; Diette & Raghav, 2017); later start times increase math and reading test scores among middle school students (Edwards, 2012); and start times that are later relative to sunrise increase math and reading scores among middle and high school students, with larger effects for older students (Heissel & Norris, 2018). Biller et al (2022) provide a complete review of extant studies of the effects of school start times on grades and test scores among adolescents worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, prior research in the United States has found that earlier course timing decreases grades among college students (Carrell et al, 2011; Diette & Raghav, 2017); later start times increase math and reading test scores among middle school students (Edwards, 2012); and start times that are later relative to sunrise increase math and reading scores among middle and high school students, with larger effects for older students (Heissel & Norris, 2018). Biller et al (2022) provide a complete review of extant studies of the effects of school start times on grades and test scores among adolescents worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence that school timing matters for student outcomes (Carrell et al, 2011; Diette & Raghav, 2017; Edwards, 2012; Heissel & Norris, 2018), prior research has produced inconsistent evidence on the effects of school start time policies on educational outcomes, as reviewed by Biller et al (2022). Though most research on high school start time changes in the United States finds that later school start times are associated with fewer late arrivals (Dunster et al, 2018; Lenard et al, 2020; Owens et al, 2010; Thacher & Onyper, 2016; Wahlstrom et al, 2014), fewer absences (Lenard et al, 2020; McKeever & Clark, 2017; Wahlstrom et al, 2014), and fewer disciplinary problems (Thacher & Onyper, 2016), some studies show null or opposite findings (Dunster et al, 2018; Fuller & Bastian, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous data showed that Argentinian students attending school in the afternoon exhibit higher levels of SJL than their Brazilian peers and similar short sleep duration than their Canadian peers attending school in the morning (Carvalho‐Mendes et al, 2020; Goldin et al, 2020; Martin et al, 2016; Rodríguez Ferrante et al, 2022a). On the other hand, the increase in the quantity and diversity of SST studies conducted across the world will allow researchers to address more specific questions, as the factors explaining the variability on the effects of later SSTs on academic performance (Biller et al, 2021; Yip et al, 2022). So far, most studies support the idea that the later the SST the better, but the economic and social implications of a SST delay are important.…”
Section: Discussionmentioning
confidence: 99%
“…First, while our paper reports cross-national variations in adolescent sleep patterns with accurate time-diary data, our data do not allow exploring the societal and cultural factors behind such variations. Scholars should dig deeper into the role of societal factors that determine adolescent sleep behavior, for example by examining cross-nationally the role of school organizations or parental control in influencing sleep patterns and other related factors, such as school performance (Biller et al, 2022;Yip et al, 2022). Second, while our time-diary approach brings a novel 24-hour look at the multiple ways in which adolescents engage in activities during the evening, we were not able to provide a precise picture of the context and content of these activities prior to sleep onset.…”
Section: Discussionmentioning
confidence: 99%